A short review of bioaerosol emissions from gas bioreactors: Health threats, influencing factors and control technologies. (August 2020) - Hu, Xu-Rui; Han, Meng-Fei; Wang, Can; Yang, Nan-Yang; Wang, Yong-Chao; Duan, Er-Hong; Hsi, Hsing-Cheng; Deng, Ji-Guang
Abstract: Bioaerosols have widely been a concern due to their potential harm to human health caused by the carrying and spreading of harmful microorganisms. Biofiltration has been generally used as a green and effective technology for processing VOCs. However, bioaerosols can be emitted into the atmosphere as secondary pollutants from the biofiltration process. This review presents an overview of bioaerosol emissions from gas bioreactors. The mechanism of bioaerosols production and the effect of biofiltration on bioaerosol emissions were analyzed. The results showed that the bioaerosol emission concentrations were generally exceeded 10 4  CFU m −3, which would damage to human health. Biomass, inlet gas velocity, moisture content, temperature, and some other factors have significant influences on bioaerosol emissions. Moreover, as a result of the analysis done herein, different inactivation technologies and microbial immobilization of bioaerosols were proposed and evaluated as a potential solution for reducing bioaerosols emissions. The purpose of this paper is to make more people realize the importance of controlling the emissions of bioaerosols in the biofiltration process and to make the treatment of VOCs by biotechnology more environmentally friendly. Additionally, the present work intends to increase people's awareness in regards to the control of bioaerosols, including microbial fragment present in bioaerosols. Highlights: The biofiltration generally emit more than 10 4  CFU m −3 bioaerosol. The bioaerosol emitted from the biofiltration is a potential threat to human body. Shear force and dilution affect the concentration of bioaerosol emissions. PCD is promising to control bioaerosols because of few secondary pollutants.